Immune Response in Melanoma: A Basis to Understand the Role of Immunotherapy with Immune Checkpoint Inhibitors - Eugénia Matos Pires; Cecília Moura (Sociedade Portuguesa de Dermatologia e Venereologia, 2018)
The knowledge of the pathophysiology of tumour progression is crucial to understand the therapeutic targets in order to control the disease. The mechanisms used by the immune system to affect cancer development and progression has been a challenging question in immunology. It is now postulated that immunology plays a dual role in this process: it protects against tumour growth, destroying "aberrant" tumour cells, but may also promote tumour progression by selecting tumour cells that are able to escape the immune response and survive in an immunocompetent host. These findings gave rise to the concept of "cancer immunoediting", which explains the influence of the immune system on tumour progression. Several observations like immunosuppression as a risk factor for melanoma, the possibility of partial or complete regression of primary tumour and development of vitiligo, have suggested that melanoma is an immunogenic tumour but a successful tumour evolution can occur in the light of the "immunoediting" concept. Immune checkpoints, cytotoxic T lymphocyte antigen (CTLA)-4 and programmed cell death (PD-1), were recognized to have important roles in regulating T cell responses during tumour development and were proven to be effective targets in treating advanced melanoma. This article will briefly review the process of tumour evolution and its interaction with the immune system as well as the mechanism of action of the immune checkpoint inhibitors to understand better the new targeted immunotherapies for advanced melanoma, that will be further discussed.